Metaphors in Contemporary Russian Foreign Policy Discourse - Skrebcova, Tatjana (Respectus Philologicus, 2002)
The article examines metaphors involved in the modern Russian political discourse on foreign affairs in the vein of seminal works by G. Lakoff, C. de Landtsheer, R. Anderson, Jr. Particular attention is drawn to conventional metaphors directly grounded in bodily experience and thus deeply embedded in the human conceptual system. Manifold correlations between perceptual and spatial concepts of the source domain are shown to be preserved in the target domain, forming a coherent system of conceptual metaphors. The paper argues that the conceptualization of foreign policy in terms of bodily experience undergoes a two-step metaphorization process.